2005
DOI: 10.1007/s00432-005-0061-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemically modified heparin inhibits the in vitro adhesion of nonsmall cell lung cancer cells to P-selectin

Abstract: These findings suggest that some chemically modified heparins with low anticoagulant activity may deserve further testing in the experimental NSCLC treatment protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…It has been reported that among various proteoglycans, the heparin sulfate-like proteoglycan molecules play an important role in the adhesion of tumor cells to P-selectin. 17,27,35 We want to know if the heparin sulfate-like proteoglycan on the A375 cell surface can act as a ligand of a IIb b 3 in the interaction of A375 cells with platelets. The enzyme treatment experiments demonstrated that the structure of heparin sulfate-like proteoglycans is responsible for the adhesion of A375 cells to a IIb b 3 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that among various proteoglycans, the heparin sulfate-like proteoglycan molecules play an important role in the adhesion of tumor cells to P-selectin. 17,27,35 We want to know if the heparin sulfate-like proteoglycan on the A375 cell surface can act as a ligand of a IIb b 3 in the interaction of A375 cells with platelets. The enzyme treatment experiments demonstrated that the structure of heparin sulfate-like proteoglycans is responsible for the adhesion of A375 cells to a IIb b 3 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that heparin or chemically modified heparins inhibited P-selectin-mediated adhesion (15,21). In this study, we prepared four chemically modified heparin deriva-tives with low anticoagulant activities (data not shown), including RO-heparin, CR-heparin, 2/3ODS-heparin and N/2/3DS-heparin, using various well-established methods.…”
Section: Resultsmentioning
confidence: 95%
“…The adhesion of tumor cells to transfected CHO cells or anchored-platelets expressing P-selectin under flow conditions (0.3 dyn/cm 2 ) was measured by real-time video microscopy as described previously (21). The number of bound cells was quantified from videotape recordings of 10-20 fields of view obtained at the end of a 3-min perfusion.…”
Section: Methodsmentioning
confidence: 99%
“…The involvement of selectins in metastasis has been shown in selectin-deficient mouse models (Borsig et al, 2002;Kim et al, 1998;O et al, 2002). Several studies have shown that heparin and heparinoids inhibit selectin-mediated cell adhesion, an important phase of metastasis (Borsig, 2010;Borsig et al, 2001;Borsig et al, 2002;Gao et al, 2006;Ma & Geng, 2000;Maraveyas et al, 2010;Stevenson et al, 2005;Stevenson et al, 2007;Varki, 2007;Wahrenbrock et al, 2003;Wei et al, 2004). To investigate the antimetastatic potency of ODSH, we used U937 cells, a human monocytic leukemia cells.…”
Section: Odsh Has Anti-metastatic and Anti-inflammatory Activities Inmentioning
confidence: 99%